Пропитка аморфного бора расплавом кремния в условиях высоких давлений и температур - Стратийчук, Д.А. (Доповіді НАН України, 2011)
Запропоновано метод одержання керамiки на базi SiB3, SiB4 та SiB6 шляхом просочування аморфного бору розплавом кремнiю в умовах високих тискiв та температур. Отримана керамiка була дослiджена методами РФА, СЕМ та РСМА. Встановлено, що високi статичнi тиски значно зменшують температуру та час взаємодiї бору iз розплавом кремнiю. Отримана в такий спосiб непориста керамiка практично не мiстить вiльного кремнiю. Показано, що при збiльшеннi тиску вiд 0,3 до 7,7 ГПа спостерiгається збiльшення густини, твердостi та трiщиностiйкостi керамiки. To obtain SiB3-, SiB4-, and SiB6-based ceramics, the method using the impregnation of amorphous boron with a silicon melt under high-pressure high-temperature conditions has been proposed. The ceramics obtained by the impregnation have been examined by the methods of X-ray diffraction phase analysis and scanning electron microscopy. It has been stated that the high static pressure considerably decreases the temperature and the time of the interaction of boron with a silicon melt. he nonporous silicon-boride-based ceramics contains no free silicon. The increase of the density, hardness, and crack resistance of the ceramics is observed, if the pressure increases from 0.3 to 7.7 GPa.